Stimulation of Enterotoxin B Production I. Stimulation by Fractions from a Pancreatic Digest of Casein - Wu, Cheng-Hsien (1971)
Chromatography on Dowex 50-X2 of Protein Hydrolysate Powder (Mead Johnson International, Evansville, Ind.), a pancreatic digest of casein, yielded 18 fractions. Five fractions stimulated enterotoxin production in greater amounts than were produced in the basal medium when it contained Protein Hydrolysate Powder. The stimulatory effect was due to the presence of peptides in the fractions. Many of these peptides contained large amounts of proline. Apparently, the primary structure of the peptides was important in the stimulation effect.